Design of a Mobile-Based Systemic Lupus Erythematosus (SLE) Self-Management Application - Diva Ivani Arista Pangastuti; Aridhanyati Arifin (Institut Teknologi Bisnis AAS Indonesia, 2025)
Lupus is a chronic autoimmune disease characterized by unpredictable cycles of remission and flare-ups, making regular monitoring of symptoms essential. However, many people with lupus experience challenges in consistently tracking their health due to brain fog, fatigue, and the wide variation of symptoms, which often leads to missed medication schedules and incomplete symptom records. This study aims to develop a mobile self-management application designed to help individuals with lupus monitor their health, manage their medications, and increase awareness of self-care activities. The development process employed the DMAIC (Define–Measure–Analyze–Improve–Control) framework, with the initial application prototype created using Figma. The prototype was tested with 22 respondents who are people with lupus (ODAPUS) to gather user feedback. The results indicate that users evaluated the application positively and found it beneficial for daily health management. Nevertheless, they recommended simplifying the interface and user flow to enhance usability. These insights will guide further improvements in the next stage of development.